Impactos da conversão de sistemas nativos em áreas de cultivo agrícola nos indicadores de qualidade do solo - Rieth, Gerry (2019)
Soil quality (SQ) is influenced by its physical, chemical and biological properties and its quantification is necessary to understand the influence of different soil management practices performed on the conversion of natural environments for agronomic uses. Changes in these soil properties are verified by soil quality indices. The objectives of this work were (i) to evaluate changes in the physical, chemical and biological properties of the soil in its different uses; (ii) determine the effects on the ground for the change of use in expanding regions of soybean cultivation; (iii) and promote the use and validation of the Soil Management Assessment Framework (SMAF) methodology to verify changes in land use in soil quality. The underlying hypothesis is that SMAF detects changes in soil quality caused by changes in land use in regions of Rio Grande do Sul. Therefore, the study was conducted in soybean expansion regions in Rio Grande do Sul. The soils and their uses analyzed were Rhodic Eutrudox, Typic Acrustox for native forest (NF), native pasture (NP), cultivated pasture (CP), soybean (SO) and Paleudalf for soil uses. NP, CP and SO. Physical and chemical samples were collected in the layers 0.0-0.10; 0.10-0.20 and 0.20-0.30 m and biological in the 0.00-0.10 m layer. In loco, the evaluation of the soil structure was carried out by the VESS (Visual Evaluation of Soil Structure) methodology. The SQ was quantified by the SMAF methodology, including the attributes pH, phosphorus (P), potassium, soil density and carbon of the microbial biomass (CMB). They were submitted to the Anova test and, when significant, the Student's t test (p <0.05) to verify the influence of land use on the physical, chemical and biological properties in each region and analysis of soil quality indices. SO and CP soil management practices negatively affected soil physical properties and favored chemical properties. Native forest obtained higher SQ than other soil uses in the Rhodic Eutrudox and Typic Acrustox. Converting NP to CP and SO reduces SQ to 65% in Paleudalf. The SMAF detected changes in QS by land use conversion, being a promising tool for QS analysis in soils of Rio Grande do Sul.